2009
DOI: 10.1016/j.jasms.2009.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical effects during [M-H] dissociations of epimeric 11-OH-17β-estradiols and distant electronic effects of substituents at C(11) position on gas phase acidity

Abstract: The affinity of estradiol derivatives for the estrogen receptor (ER) depends strongly on nature and stereochemistry of substituents in C (11) position of the 17␤-estradiol (I). In this work, the stereochemistry effects of the 11␣-OH-17␤-estradiol (III ␣ ) and 11␤-OH-17␤-estradiol (III ␤ ) were investigated using CID experiments and gas-phase acidity (⌬H°a cid ) determination. The CID experiments showed that the steroids decompose via different pathways involving competitive dissociations with rate constants de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…A method has been proposed [33,34] and used [35][36][37] to estimate the enthalpies of fragmentations from these curves. To this end, it was suggested to consider the phenomenological appearance energy AEs (AEexp), i.e.…”
Section: Resultsmentioning
confidence: 99%
“…A method has been proposed [33,34] and used [35][36][37] to estimate the enthalpies of fragmentations from these curves. To this end, it was suggested to consider the phenomenological appearance energy AEs (AEexp), i.e.…”
Section: Resultsmentioning
confidence: 99%
“…9), in agreement with the ability of these compounds to either up Hydrogen bridges involved in E 2 binding (3-OH and 17β-OH), which contribute to the displacement of H12 [5], are found here to be essential for optimal LxxLL recruitment. We show in this study that small hydrophobic substituents in C-11β, as well as the introduction of shows an unexpected behavior that could be relevant to electronic effects [28]. In fact, the nature of the interactions between ligand substituents and the LBD most likely influence the affinity of ERα for coactivators since (-CH 3 ) versus (-CH 2 Cl and -C CH) gave distinct LxxLL binding profiles.…”
Section: Relationship Between Ligand-induced Recruitment Of Coactivatmentioning
confidence: 75%
“…indicating that particular electronic effects occur in 11β-OH E 2 [28]. Polarity appeared nevertheless of prime importance for LxxLL-containing coregulators recruitment because produced a shift in ERα-LxxLL binding (as compared to the curve generated by E 2 ), similar to that produced by the grafting of -CH 2 Cl of -C CH groups, revealed that it is the whole region around C-11 which exerts an influence on LxxLL recruitment (Fig.…”
Section: Influence Of Substitutions In C-11 Of Estradiolmentioning
confidence: 84%
“…[1] Some aspects of the MS fragmentation of estradiol have been previously addressed. [3,14,15] However, ion structures of important fragments observed in the mass spectrum have not been identified. For example, m/z 244 peak in the EI spectrum of estradiol has been suggested to arise inconclusively from loss of either CO or C 2 H 2 .…”
Section: Introductionmentioning
confidence: 99%